Development of "Serasa" Media to Improve Understanding and Learning Outcomes of Nusantara Kingdom Materials - Herawati Cahya Kusumasari; Sri Sukasih (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
Natural and Social Sciences (IPAS) learning in grade IV of SDN Ngaliyan 05 faces several problems, especially related to the dominant learning method using lectures without the support of interesting learning media. This condition causes a lack of students' attention and understanding of the material, resulting in low learning outcomes. To overcome these problems, this study aims to develop an interactive learning media based on Articulate Storyline called "Serasa" using the ADDIE development model. The study results showed that the "Serasa" media was feasible, as evidenced by the validation score of 86% of media experts, 88.3% of material experts, and 88.3% of practitioners. In addition, this media has proven to be effective in improving students' understanding and learning outcomes on royal materials in the archipelago, which is shown by the t-test with a significance value (2-tailed) < 0.05 and the N-gain test on a large scale, namely 0.6559 for multiple-choice questions and 0.6542 for description questions. Thus, the "Serasa" media can be used to improve the quality of learning in the fourth grade, especially in the material of royal history in the archipelago.